Episodes in the Malaysian auditing saga - Ali, Azham; Haniffa, Roszaini; Hudaib, Mohammad (Emerald Group Publishing Limited, 2006)
Purpose – The purpose of this paper is to examine the various episodes in the Malaysian auditing saga, covering the period of the first 40 years post-independence in 1957 to just before the onset of the Asian Financial Crisis in 1997.Design/methodology/approach – Based on documentary analysis, the paper offers a historical account of the development of the auditing profession with reference to the dynamic changes in its political and socio-economic environment. Findings – The paper concludes that the function of auditing in Malaysian society responded to political-economic pressures over time viz. changing from maintaining the economic policy to serve Western investors to accommodating ethnic relations, and to strengthening the bond between local and global corporate elites and the political leaders.Originality/value – Since, little is known of the professionalisation process in Malaysia, our analysis of the structural conditions during the 40 years from the achievement of independence from the British in 1957 to just before the onset of the Asian Financial Crisis in 1997 and our assessment of their implications for auditing contributes to knowledge in this area.